Serum Level of Antibodies Against Novel Acinetobacter Baumannii OmpA-selected Peptides in ICU Staff: Promise for the Future of Vaccine Development - Shadi Paydarfar; Mohammad Amin Abbasi; Ali Hashemi; Sodabe Taheri; Mojgan Bandehpour; Nariman Mosaffa (Iranian Journal of Allergy, Asthma and Immunology, 2023)
Extensively drug-resistant Acinetobacter baumannii is considered one of the most dangerous threats to global health, requiring novel therapeutic interventions. The outer membrane protein A (OmpA) is an immunogenic agent that triggers immune responses. The current study evaluated serum antibody levels against previously determined immunogenic OmpA peptides from A baumannii in ICU staff. Serum samples were collected from 62 ICU staff members (representing the exposed group), healthy controls (representing the nonexposed group), and patients with systemic lupus erythematosus (SLE) (as controls for nonspecific antibody reactions). After excluding the cross-reactive antibodies via Escherichia coli lysate pretreatment, all the samples were assessed in the vicinity of A baumannii lysate by enzyme-linked immunosorbent assay (ELISA). All the positive samples were assessed for interaction with previously designed and selected peptides using ELISA. The protective potential of positive serum antibodies was surveyed in vitro using an opsonophagocytic study. The most antibody positive samples against one of the dominant peptides were determined in the ICU personnel (75%).  SLE serum samples did not react with candidate peptides. The strongest positive reaction was observed in serum treatment with one of the OmpA peptides (No. 5) with significant differences compared to other designed peptides. Our findings showed that ICU samples have substantially higher antibody levels than the nonexposed group; Positive samples show strong results in the opsonophagocytosiis assay. This study demonstrates A baumannii colonization at human mucosal surfaces, especially in exposed healthy workers. Novel OmpA-derived peptides could be used to identify immunogenic vaccine candidates. Therefore, more studies are needed  before this peptide and antibody levels are used in diagnosis, prevention, or treatment.